Comparative Analysis of Color Video Enhancment Techniques - Sunakara, Rajeev; Sankar, P.Ravi (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Contrast enhancement has an important role in image processing applications. This paper presents a color enhancement algorithm based on adaptive filter technique. First, the proposed method is divided into three major parts: obtain luminance image and backdrop image, adaptive modification and color restoration. different traditional color image enhancement algorithms, the adaptive filter in the algorithm takes color information into consideration. The algorithm finds the significance of color information in color image enhancement and utilizes color space conversion to obtain a much better visibility. In the practical results, the proposed method reproduces better enhancement and reduce the halo distortion compared with the bilateral methods.